2012
DOI: 10.5601/jelem.2013.18.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of potassium, calcium and magnesium by selected species of grassland legumes and herbs

Abstract: The study was conducted in 1998-2000, in the Olsztyn Lakeland, on permanent grassland communities with at least 5% share of the following leguminous and herbaceous species. Trifolium pratense, Trifolium repens, Lotus corniculatus, Lathyrus pratensis, Lotus uliginosus, Vicia cracca, Taraxacum officnale, Achillea millefolium, Plantago lanceolata, Alchemilla vulgaris, Heracleum sibiricum and Cirsium oleraceum. In total, 444 plant samples were analyzed, including 123 collected on organic soils. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…The highest concentration of this metal 0.211 mg•kg -1 , was found in chamomile. Results of the performed analyses comply with studies of other authors who found that, depending of the species, plant organ and harvesting site, herbs are likely to contain trace or larger amounts of cadmium; however, never exceeding 0.3 mg•kg -1 of dry matter (Rozporządzenie Ministra Zdrowia, 2003;Blicharska et al, 2008;Grzegorczyk et al, 2013). All the investigated herbal infusions showed, from the point of view of nutrition, a significant total polyphenol content, ranging from 323.84 to 752.84 mgGAE•cm -3 ( Figure 1).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The highest concentration of this metal 0.211 mg•kg -1 , was found in chamomile. Results of the performed analyses comply with studies of other authors who found that, depending of the species, plant organ and harvesting site, herbs are likely to contain trace or larger amounts of cadmium; however, never exceeding 0.3 mg•kg -1 of dry matter (Rozporządzenie Ministra Zdrowia, 2003;Blicharska et al, 2008;Grzegorczyk et al, 2013). All the investigated herbal infusions showed, from the point of view of nutrition, a significant total polyphenol content, ranging from 323.84 to 752.84 mgGAE•cm -3 ( Figure 1).…”
Section: Resultssupporting
confidence: 87%
“…They also reduce the risk of cancer, diabetes, athero-sclerosis and nervous system and cardiovascular diseases. Products with high content of phenolic compounds, such as fruits and vegetables, green tea or some herbs, consumed as part of a daily sustainable diet, may produce health promoting effects (Scalbert et al, 2005;Grzegorczyk et al, 2013;Raza et al, 2013;Kozak at al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat conditions have a significant effect on the quantitative and qualitative composition of grassland communities comprising numerous species of grasses, legumes, sedges (Cyperaceae), herbs and weeds. The characteristics of grassland habitats are an important consideration since they affect the chemical composition of green forage (TR¥BA, WY£UPEK 1998, TRZASKOOE et al 1998, TR¥BA, WOLAÑSKI 2003, GRZEGORCZYK et al 2004, 2011. According to TR¥BA (1997), forage obtained from grasslands with a high share of dicotyledonous plant species is a rich source of phosphorus, magnesium, calcium and sodium, but it has a low potassium content.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations indicate the risk of depleting soil magnesium resources if this element is not returned to soil, especially when large doses of nitrogen or potassium diversify and stimulate plant communities, thus raising several-fold the uptake of magnesium with the plant yield (WiśnioWska-kielian, stępień-olkuśnik 2001, Hejcman et al 2006, Burzyńska 2009, grzegorczyk et al 2013, kopeć and gondek 2015.…”
Section: Introductionmentioning
confidence: 99%